Introduction of Early Science Learning through Open Inquiry Approach on 5-6 Years Old Children at TK Muslimat NU 14, Kendal - Andikawati, Lina; Diana, Diana (BELIA: Early Childhood Education Papers, 2017)
The purpose of this study is to determine the effectiveness of open inquiry approach in introducing the early science learning to 5-6 years old children at TK Muslimat NU 14, Kendal. The type of this study is pre-experimental design with one group pretest-posttest design. The sampling applied purposive sampling technique with group B of TK Muslimat NU 14 Plantaran as experimental class. Hypothesis test in this study applied paired sample t-Test calculation obtained from pretest and posttest results. The t-test result obtained t value of -14.777 with significance (2-tailed) 0.000 <0.05, which means there is a significant difference between the value of pretest and posttest. The mean is -12.76. The minus sign indicates that the average of the first group (pretest data) is smaller than the second group (posttest data). So, HO is rejected and Ha is accepted. It shows that there is difference of mean of pretest and posttest value. It can be concluded that the open inquiry approach is an effective approach used for the introduction of early science learning on 5-6 years old children. Keywords: Open Inquiry approach, early science learning